Penghayatan Selibat Imam sebagai Kesaksian Hidup di Zaman Sekarang - Yohanes Hario Kristo Wibowo (Jurnal Teologi (Journal of Theology), 2017)
Celibacy as a living testimony calls for a re-interpretation on its meaning. Re-engagement on celibacy is sought by reflecting deeply and discovering the richness of its meaning and value, especially through the Scriptures and Church Documents. The attempt to interpret the meaning of celibacy aims to discover the privilege of that choice of life. That privilege is necessary for celibacy to be an inspiring and truly relevant life choice in today's world. Celibacy will increasingly become a living witness for the people today, when is lived with joy by the priests and religious with the support of the faithful and the grace of God. Thus, celibacy becomes a viable choice of life to be appreciated and championed. How to love, how to serve, and way of life are three points of re-interpretation of the meaning of celibacy as a testimony. These three ways are an approach that needs to be endeavored and lived continuously so that celibacy becomes a meaningful witness of life for the Church and does not close the possibility of being a testimony to the people around them.